Palimpsest on freud (1992)
Freud's life and works are viewed on the light of his precedents in the natural and cultural sciences. The "palimpsest" concept is used to this purpose. Such concept was first employed in a metaphorical mood by Thomas de Quencey, but his content is here amplified. In this terms, Freud' s development is resumed on five items: cocain and hypnosis, self-analysis and psychoanalytical dialogue, children's sexuality, death and religion.